Ambient Electrosynthesis of Ammonia on a Core–Shell‐Structured Au@CeO2 Catalyst: Contribution of Oxygen Vacancies in CeO2. Issue 23 (22nd March 2019) - Liu, Guoqiang; Cui, Zhiqing; Han, Miaomiao; Zhang, Shengbo; Zhao, Cuijiao; Chen, Chun; Wang, Guozhong; Zhang, Haimin
Abstract: Electrosynthesis of NH3 through the N2 reduction reaction (NRR) under ambient conditions is regarded as promising technology to replace the industrial energy‐ and capital‐intensive Haber–Bosch process. Herein, a room‐temperature spontaneous redox approach to fabricate a core–shell‐structured Au@CeO2 composite, with Au nanoparticle sizes below about 10 nm and a loading amount of 3.6 wt %, is reported for the NRR. The results demonstrate that as‐synthesized Au@CeO2 possesses a surface area of 40.7 m 2  g −1 and a porous structure. As an electrocatalyst, it exhibits high NRR activity, with an NH3 yield rate of 28.2 μg h −1  cm −2 (10.6 μg h −1  mg −1 cat., 293.8 μg h −1  mg −1 Au ) and a faradaic efficiency of 9.50 % at −0.4 V versus a reversible hydrogen electrode in 0.01 m H2 SO4 electrolyte. The characterization results reveal the presence of rich oxygen vacancies in the CeO2 nanoparticle shell of Au@CeO2 ; these are favorable for N2 adsorption and activation for the NRR. This has been further verified by theoretical calculations. The abundant oxygen vacancies in the CeO2 nanoparticle shell, combined with the Au nanoparticle core of Au@CeO2, are electrocatalytically active sites for the NRR, and thus, synergistically enhance the conversion of N2 into NH3 . Abstract : Room at the active site : A room‐temperature redox approach is used to prepare a composite core–shell‐structured Au@CeO2 electrocatalyst (see figure) composed of small gold nanoparticles (<10 nm) and rich oxygen vacancies in CeO2 nanoparticles to synergistically boost the electrocatalytic activity toward the N2 reduction reaction (NRR) to NH3 .